Teologia Prática desde uma perspectiva Latino-Americana e Caribenha (Razão e Fé, 2023)
The aim of this essay is to enable a reflection from Brazil and Latin America in the light of Christian theology that needs to assume the challenges that emerge from life, from the reality of people and our societies, permanently threatened by violence, inequalities in all senses and by constant threats to the democratic system. Thus, we understand that our reflection and our faith journey must not be seen in an individualistic way, alienated from human dramas and from the environment itself, nowadays extremely threatened by the projects of big companies and even of governments and their strategic plans. Theology among us is not limited to debates within our churches. If we listen to the Gospel of Jesus and take it seriously in our life and faith, it must assume the pains of the world and of our people, as we sing in the Kyrie - Have mercy, Lord!